2018
DOI: 10.1136/neurintsurg-2018-014363
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline shield with single antiplatelet therapy in aneurysmal subarachnoid haemorrhage: multicentre experience

Abstract: BackgroundThe Pipeline Embolisation Device with Shield technology (PED-Shield) is suggested to have reduced thrombogenicity. This reduced thrombogenicity may make it possible to use safely in the acute treatment of aneurysmal subarachnoid haemorrhage (aSAH) on single antiplatelet therapy (SAPT).ObjectiveTo evaluate the safety and efficacy of the off-label use of PED-Shield with SAPT for the acute treatment of aSAH.MethodsPatients who underwent acute treatment of ruptured intracranial aneurysms with the PED-Shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 23 publications
0
79
1
Order By: Relevance
“…Recent advances in polymer coating technology have led to FDS with reduced thrombogenicity becoming available (e.g., PED Shield; Medtronic). Maning et al [9] used the PED Shield under SAPT to treat 14 patients with aSAH and reported no difference in the rate of acute stent thrombosis, permanent morbidity, or mortality compared with the meta-analysis performed by Cagnazzo et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in polymer coating technology have led to FDS with reduced thrombogenicity becoming available (e.g., PED Shield; Medtronic). Maning et al [9] used the PED Shield under SAPT to treat 14 patients with aSAH and reported no difference in the rate of acute stent thrombosis, permanent morbidity, or mortality compared with the meta-analysis performed by Cagnazzo et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Furthermore, the concept of enhanced platelet recovery was recently discussed in relation to the PED Shield. 6 Although aspirin could be used in conjunction with coated devices, such as the p48_HPC, the potential for inadequate antiplatelet activity was considered too great especially because these were the first cases evaluated in human patients. For these reasons, aspirin is not currently considered to be the optimal antiplatelet agent in these patients.…”
Section: Demographicsmentioning
confidence: 99%
“…Its rapid onset of action and short half-life make it an attractive alternative to the oral thienopyridine agents in the acute phase of SAH, but the clinical experience is still minimal, and the high price is a significant disadvantage [26]. A promising recent advancement has been the surface modification to reduce the inherent thrombogenicity of FDS [27][28][29]. Manning et al used the PED with shield technology under single antiplatelet therapy in treating 14 patients with ruptured intracranial aneurysms and reported no hemorrhagic or thromboembolic complications in the subgroup that did not receive postinterventional heparin infusion [29].…”
Section: Management Of Antiplatelet Therapymentioning
confidence: 99%
“…A promising recent advancement has been the surface modification to reduce the inherent thrombogenicity of FDS [27][28][29]. Manning et al used the PED with shield technology under single antiplatelet therapy in treating 14 patients with ruptured intracranial aneurysms and reported no hemorrhagic or thromboembolic complications in the subgroup that did not receive postinterventional heparin infusion [29]. Until establishing the efficacy and safety of such coatings in a large clinical trial, the use of FDS will remain limited by the need for DAPT.…”
Section: Management Of Antiplatelet Therapymentioning
confidence: 99%